Information Processing in the Formation of Students' Morals: Cognitive-Behavior Perspectives and Qur'anic Values - Manan, Samiro; Nasrullah, Muhammad; Sumaji, Sumaji (Journal of English Language and Education, 2026)
Islamic boarding schools (pesantren) in Indonesia have long been recognized as indigenous educational institutions that play a strategic role in shaping individuals with strong moral and religious character. This study aims to analyze the mechanism of moral character formation among pesantren students through the integration of Information Processing Theory, the Cognitive-Behavior perspective, and Qur’anic values. The research employs a qualitative library research approach focusing on conceptual analysis and theoretical synthesis rather than field-based numerical data. Data sources consist of primary references such as the Qur’an and authoritative works in cognitive and educational psychology, supported by secondary sources including accredited journals and classical as well as contemporary Qur’anic commentaries. Data were collected through systematic documentation and analyzed using descriptive content analysis following the interactive model of Matthew B. Miles and A. Michael Huberman. The findings reveal that moral formation in pesantren is not an instant or mystical process, but a structured cognitive-spiritual mechanism involving attention, encoding, storage, and retrieval of moral information reinforced by repetition, modeling, and reflective practices. The Cognitive-Behavior framework underscores the significant role of the kyai as a living model shaping students’ belief systems and behavioral schemas, while Qur’anic concepts such as tadabbur, tazkiyatun nafs, and muraqabah function as metacognitive and spiritual control mechanisms. Theoretically, this study contributes by proposing an integrative conceptual model that bridges modern cognitive psychology and Islamic educational thought, demonstrating that moral character formation can be systematically explained through information-processing architecture enriched by cognitive-behavioral constructs and grounded in Qur’anic epistemology. This model extends the application of Information Processing Theory beyond academic learning into the domain of moral education, recontextualizes Cognitive-Behavior principles within a faith-based institutional setting, and offers a multidisciplinary framework for understanding character education as a structured cognitive-spiritual process. The study concludes that pesantren education represents an integrated cognitive-spiritual ecosystem that systematically cultivates sustainable moral character.